Investigation of preoperative physical activity level in kidney transplant recipients and its impact on early postoperative recovery: A retrospective cohort study - Li, Guo; Guo, Qi-fan; Zhao, Shang-ping; Wang, Miao-wei; Zhang, Xia; Wang, Ao; Gui, Chen-fan; Tan, Qi-ling; Gao, Qiang (Frontiers in Surgery, 2023)
Objective To retrospectively investigate the preoperative physical activity (PA) level in kidney transplant recipients (KTRs) and its impact on early postoperative recovery. Methods A total of 113 patients who received kidney transplantation at West China Hospital of Sichuan University were enrolled in this retrospective cohort study. According to the PA level measured by the Chinese version of the International Physical Activity Questionnaire—Long Version, the patients were allocated into the low PA level group (Group L, n = 55) and medium to high PA level group (Group MH, n = 58). The kidney function recovery indicators, including estimated glomerular filtration rate (eGFR), postoperative complications, postoperative length of stay (LOS), and unscheduled readmission within three months of discharge, were evaluated and documented. A association analysis was applied to analyze and compare the association between indicators. Results The median PA levels of the KTRs were 1701.0 MTEs * min/week. Regarding the postoperative recovery indicators, the KTRs spent a mean time of 19.63 h to achieve transfer out of bed after the operation (Group L: 19.67 h; Group MH: 19.53 h; P = 0.952) and reached a mean distance of 183.10 m as the best ambulatory training score within two days after the operation (Group L: 134.91 m; Group MH: 228.79 m; P < 0.001). The preoperative PA level showed a moderate positive association with early postoperative ambulation distance (ρ = 0.497, P < 0.001). However, no significant between-group difference in eGFR on postoperative days 1, 3, and 5 (P = 0.913, 0.335, and 0.524) or postoperative complications, including DGF (P = 0.436), infection (P = 0.479), postoperative LOS (P = 0.103), and unscheduled readmission (P = 0.698), was found. Conclusions The preoperative PA level of KTRs is lower than that of the general population. KTRs with moderate or high preoperative PA levels showed higher ambulatory function in the early postoperative period than those with low preoperative PA levels, but no between-group differences in other early recovery indicators were observed.